Review of Indonesian Language Subject Textbooks in Elementary Schools - Nurhikmah; Rahma Ashari Hamzah; Samsinar Suedi (Universitas Islam Lamongan, 2026)
The curriculum applicability, content quality, language use, and integration with literacy-based learning of Indonesian language textbooks in primary schools were the main topics of this study, which employed library research methodologies. This study is classified as library research because it is grounded in the literature. Research that gathers information from multiple sources is known as library research. Books are only one type of literature that can be studied; other types include newspapers, periodicals, magazines, and documents. Finding different theories, laws, propositions, principles, opinions, ideas, and other sources that can be utilized to examine and resolve the issues under study is the main goal of library research. According to the findings, there are still serious flaws in some textbooks even though they fulfill curriculum requirements. These include a lack of interactive features, a lack of diversity in reading materials, and a poor integration of contextual and cultural factors. Incorporating project-based activities, personal reflection, visual mapping, and multi-genre readings that are relevant to students' life into textbooks is advised in order to promote active and creative learning. More stimulating, conversational, and cognitively developmentally appropriate language should also be employed. It is anticipated that these suggestions will provide authors and book producers with useful direction when they write instructional materials that are both educational and transforming.